High efficiency solution processed fluorescent yellow organic light-emitting diode through fluorinated alcohol treatment at the emissive layer/cathode interface - Ng, C.Y.B.; Yeoh, K.H.; Whitcher, T.J.; Talik, N.A.; Woon, K.L.; Saisopa, T.; Nakajima, H.; Supruangnet, R.; Songsiriritthigul, P. (Institute of Physics, 2014)
We compare solvent treatments using fluorinated alcohol (2,2,3,3,4,4,5,5-octafluoro- 1-pentanol) and ethanol in improving the efficiency of a polymer organic light-emitting diode (OLED) by spin coating the solvent on top of the emissive layer. The presence of fluorinated alcohol is confirmed using x-ray photoelectron spectroscopy. The electron current is found to be significantly enhanced following solvent treatment while the hole current remains the same. The solvent treatment by fluorinated alcohol on top of a 'super-yellow' poly-(p-phenylenevinylene) (SY-PPV) based OLED results in efficiency as high as 19.2 lm W−1 (20.9 cd A−1) at a brightness of 1000 cd m−2. The improvement of device efficiency through the use of fluorinated alcohol treatment can be attributed to its large dipole, which lowers the electron injection barrier. This work also suggests that fluorinated alcohol might be a better trap passivator for electrons than ethanol.